Conocimientos sobre la prueba de Papanicolaou en mujeres en edad fértil del Barrio Clodoveo Jaramillo de Loja - Jiménez Abad, Miriam Marisol (2018)
Papanicolaou test (PAP) is an exfoliative cytological sample study, widely used in cervical cancer screening allowing detecting it early. In developed countries they have shown that the usage of this test is effective in order to reduce the incidence rates and mortality from cervical cancer. The present investigative work is aimed to determine the knowledge about the papanicolaou test in women of childbearing age in Clodoveo Jaramillo neighborhood of Loja. It was descriptive type of cross sectional. The technique used for data collection was a randomized survey to 86 women of childbearing age in the period September 2017 - August 2018, finding that 49% were aged between 15 and 29 years of age. 41% are married, 30% are housewives, 48% with secondary level of education and most of them profess the Catholic religion. In what regards to knowledge, more than 60% of the respondents know about the definition anatomical site of the woman where the sample for the examination is taken; the purpose of the test, when the woman should start the test and its frequency. However, 52% report not knowing the conditions they must take into account before having the papanicolaou test. In practice, 66% have taken the test as a means of preventing cervical cancer and they have done it on their own initiative. KEY WORDS: cervical cancer, cervical cytology, knowledge.